Dear Brothers and Sisters: Pope's Speeches and the Dynamics of Conflict in Africa - (:unkn) unknown (My University, 2025)
Public speeches by leaders can serve as a cost-effective tool for fostering peace, yet their effectiveness remains uncertain, particularly in divided societies experiencing violent conflict. This paper examines the impact of the Catholic Pope's peace-promoting speeches on conflict dynamics in Africa. To investigate this, we construct a novel dataset covering all papal speeches explicitly addressing violent conflict events in Africa between 1997 and 2022. Using event-study methods, we find that papal speeches reduce overall conflict by 23% on average. However, these effects vary significantly depending on the Pope delivering the speech. While Pope John Paul II and Pope Francis's speeches are associated with substantial reductions in conflict, Pope Benedict XVI's speeches show no significant overall effect but are linked to increased battles and religious violence. We further explore four mechanisms driving these heterogeneous effects. First, the impact of papal speeches is significantly stronger in areas with a Catholic presence, where violence drops by up to 69%. Second, the effectiveness of a speech depends on the bishops' ideological alignment with the Pope's vision, with speeches delivered by a Pope who appointed the current bishop being 17% more effective. Third, political leaders play a crucial role in amplifying the Pope's message, as violence significantly declines in birth regions of national leaders. Finally, the response of armed groups varies depending on their religious affiliation and prior history of violence.
Keywords: African Research